Fostamatinib for the treatment of Japanese patients with primary immune thrombocytopenia: A phase 3, placebo‐controlled, double‐blind, parallel‐group study. (5th December 2022) - Kuwana, Masataka; Ito, Tomoki; Kowata, Shugo; Hatta, Yoshihiro; Fujimaki, Katsumichi; Naito, Kensuke; Kurahashi, Shingo; Kagoo, Toshiya; Tanimoto, Kazuki; Saotome, So; Tomiyama, Yoshiaki; ,
Summary: Fostamatinib, a spleen tyrosine kinase inhibitor, has been approved for the treatment of chronic primary immune thrombocytopenia (ITP) in the United States, Canada and some European countries. We conducted a phase 3, placebo‐controlled, double‐blind, parallel‐group study to evaluate the efficacy and safety of fostamatinib in Japanese patients with primary ITP. Thirty‐four patients were randomised to fostamatinib ( n = 22) or placebo ( n = 12) at 100–150 mg twice a day for 24 weeks. Stable responses (platelet ≥50 000/μl at ≥4 of the 6 visits from weeks 14 to 24) were observed in eight (36%) patients on fostamatinib and in none of the patients on placebo ( p = 0.030). Overall responses (platelet ≥50 000/μl at ≥1 of the 6 visits from weeks 2 to 12) were seen in 10 (45%) patients on fostamatinib and in none of the patients on placebo ( p = 0.006). Patients on fostamatinib required rescue medication less often and experienced fewer bleeding symptoms than patients on placebo. Adverse events observed were mild or moderate and were manageable. No new safety signals were identified in Japanese patients with ITP.